Effects of harvesting age, drying, tea form, storage and infusion time on physicochemical characteristics of Clinacanthus nutans (Burm. F) Lindau - Mohamad, Munirah (2017)
One of the main herbs well known for its medicinal value is the Sabah snake grass or ‘Belalai gajah’ (Clinacanthus nutans). The primary chemical constituents of the leaves are schaftoside, vitexin, isovitexin, orientin and isoorientin, and antiviral activity is shown by two glycoglycerolipids. Despite the importance of C. nutans, complete information with respect to commercial production and postharvest handling, such as plant vegetative stage (young and mature), drying method (oven, sun, solar and air), storage form (powdered and shredded) and storage duration (0, 4, 8 and 12 weeks) of the herb in the local herbal industry is still lacking. Thus, the objective of this study was to determine the optimum postharvest handling processes that could retain the physicochemical quality of C. nutans. Results of Experiment 1 showed that moisture content of all drying method were not more than 15%. In addition, it indicated that colour (L*, C* and h°), chlorophyll content, phytochemical properties and flavonoid compounds (orientin, isoorientin, vitexin, isovitexin and schaftoside) were higher in the young vegetative stage than mature vegetative stage. All the physicochemical qualities were highest when the samples were oven dried compared to the sun, air and solar dried. Furthermore, microbial contamination was not more than the permissible limit by World Health Organisation (WHO). A further study in Experiment 2 showed that the powdered sample resulted in highest phytochemical properties and flavonoid compounds compared to the shredded form. In general, 3 months of storage did not affect the C. nutans quality. Experiment 3 focused on comparing the effect of infusion time of C. nutans tea at young vegetative stage, oven dried and in powdered form (from Experiment 1 and 2) with C. nutans teas available in the local market. The colour, phytochemicals properties and flavonoid compounds infused at 2 and 5 min were significantly different. Increased infusion time at 5 min yield more phytochemical properties and flavonoid compounds than those infused at 2 min. Tea from different producers showed great distinction in their physicochemical and safety level. It was observed that the quality properties of the teas examined were considerably at second place in comparison with those of the C. nutans teas available in the local market. Fortunately, microbial and heavy metal contaminations for all producers were not more than the permissible limit by WHO. As conclusion young-oven dried and powdered form contained highest value in physicochemical characteristics during postharvest handling of Clinacanthus nutans.